Nomenclatural corrections to Australian species of Cricotopus (Wulp) (Diptera; Chironomidae) - Cranston, Peter S.; Krosch, Matt N. (Zootaxa, 2015)
Our attention has been drawn to lapsi and errors in a recent publication in this journal concerning Cricotopus Wulp (Diptera: Chironomidae) (Drayson et al., 2015).